2015
DOI: 10.1007/s12178-015-9270-2
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of interest in research: looking out for number one means keeping the primary interest front and center

Abstract: Conflicts of interest represent circumstances in which professional judgments or actions regarding a primary interest, such as the responsibilities of a medical researcher, may be at risk of being unduly influenced by a secondary interest, such as financial gain or career advancement. The secondary interest may be financial or non-financial, and the resultant bias may be conscious or unconscious. The presence of conflicts of interest poses a problem for professional, patient, and public trust in research and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 35 publications
0
25
0
1
Order By: Relevance
“…Conflicts of interest (COIs) occur when researchers stand to benefit from studies that show particular outcomes (Gorman, 2018; Institute of Medicine, 2002). In this circumstance, researcher conduct in service of producing high quality, objective research may be compromised by competing interests such as advancing one’s career or receiving immediate financial incentives (Romain, 2015). Researcher conduct can refer to a variety of activities, such as those involved in designing the study, recruiting and allocating participants to treatment and control groups, data analysis, and interpreting and reporting study findings.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicts of interest (COIs) occur when researchers stand to benefit from studies that show particular outcomes (Gorman, 2018; Institute of Medicine, 2002). In this circumstance, researcher conduct in service of producing high quality, objective research may be compromised by competing interests such as advancing one’s career or receiving immediate financial incentives (Romain, 2015). Researcher conduct can refer to a variety of activities, such as those involved in designing the study, recruiting and allocating participants to treatment and control groups, data analysis, and interpreting and reporting study findings.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of financial, commercial, legal, or professional relationship of the researcher/clinician with external agencies that could influence the outcome of a study (bias) should be disclosed explicitly and reported as a conflict of interest. This is essential as any personal interests can create bias in a study (Bekelman et al, 2003; Romain, 2015). The conflict‐of‐interest statement should also include relationships such as patent or stock ownership, membership in a company, membership of an advisory board or committee within a company, and consultancy for or receipt of speaker's fees from a company.…”
Section: The Prile 2021 Explanation and Elaboration Documentmentioning
confidence: 99%
“…In addition, non-financial benefits including recognition, career advancement, advocacy for a strongly held position, and support for friends and colleagues can also affect the research work and result biases in the research. These biases, when hidden, can affect clinical decision-making by making interventions appear safer or more effective than they really are [ 24 ].…”
Section: Conflict Of Interestmentioning
confidence: 99%